(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study was carried out with many ecological components in connection to the variety and distribution of birds along the Pravara River in Ahmednagar, India. Numerous habitat types, such as riparian forests, agricultural fields, wetlands, and grasslands, have been the subject of bird surveys. Analyses were performed on data related to flora cowl, water satisfactory indices, and the depth of human activity. There are 182 bird species in all, organised into 33 clusters. With 120 species, riparian forests had the best species richness, followed by grasslands (45 species), wetlands (52 species), and agricultural fields (78 species). There were terrific variations in the species composition of the various ecosystems. Vegetation cover (r = 0.79, p < 0.01) and dissolved oxygen degrees (r = 0.98, p < 0.01) showed a high-quality correlation with chook diversity. On the other hand, a bad affiliation (r = -zero.97, p < 0.01) was observed between the depth of human activity and avian variety. These results mean that human disturbance, habitat quality, and water quality are the primary variables affecting birds diversity and distribution along the Pravara River. The study’s findings spotlight how crucial riparian forests are to maintaining the sort of birds living in the Pravara River watershed. Along with improving water quality and lowering human disturbance, these woods offer critical habitat for a number of birds species. The need for sustainable land-use practices is highlighted by the finding that bird diversity is lower in places with heavy agricultural and human activity. The protection and restoration of riparian forests, more advantageous water quality, encouragement of sustainable land-use practices, lessening of human disturbance, and long-term monitoring of bird populations and ecological factors need to be the main objectives of conservation measures. We can assure the diversity and richness of birds inside the Pravara River basin and contribute to the overall well-being and sustainability of the surroundings by putting those suggestions into practice.